Slowed Down Economisation: The Persistence of Alternative Trade Organisations - Arnold Nadine; Hammer Isabel (Swiss Journal of Sociology, 2018)
Have Swiss Alternative Trade Organizations (ATOs) valorized economic aspects at the expense of their social mission for the longer term? From a historical perspective (1974–2013), this article shows how these social enterprises have maintained their social purpose and inhibited the course of organizational economization. We identify three deceleration strategies: involving volunteers, direct trading partnerships with producers, focusing on the sales niche. The article shows how and why economization processes are malleable and not inevitable.